PEMANFAATAN MEDIA PODCAST DALAM PRAKTIK PIDATO DAN PUISI UNTUK MENINGKATKAN PERCAYA DIRI GURU SERTA MENEMUKAN BAKAT DAN MINAT SISWA - Najlatun Naqiyah; Sifak Indana; Shobri Firman Susanto; Nonik Indrawatiningsih; Ahmad Bashri; Muhamad Sholeh; Mohammad Syahidul haq (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to boost teachers' confidence and help discover students' talents and interests through the use of podcast media in speech and poetry practices at SDN Tebon. The low confidence of teachers in delivering oral-based material and the limited outlets for student expression are the background reasons for this activity. The activity was attended by 20 participants, consisting of 10 teachers from SDN Tebon and 10 teachers from PAUD Kelurahan Tebon. The methods used included situation and condition analysis, microlearning, modeling & demonstration teaching, instructional practice, and reflection. Evaluation results showed a significant increase in post-test scores compared to pre-test, with an average gain of 20.98%. The most important improvement was observed in indicators directly related to the use of podcasts, including recording skills, understanding the benefits of the medium in learning, and teaching students to speak clearly. This training successfully equipped teachers with innovative skills to integrate digital technology, boost their confidence in teaching, and effectively develop students' talents and interests in speech and poetry reading.